An examination of audit functions: Accounting students’ perspective - Ramlan, Mohd Raime; Mohamed Noor, Mohd Naimi; Danila, Raudah (2009)
The objective of this study is to examine the auditing function which serves the users of financial statements.The financial statements have been accepted as major sources for a company financial position where interested external parties based in their decision-making process.In addition, the auditor is expected to enhance the quality of financial report; that its reliability, credibility and comparability through a proper and competent course of audit.This study has selected students of higher learning institution.The researcher replicates a survey from Reynolds (1989) to examine how respondents actually view the audit functions in terms of its importance and effectiveness.The total mean for each variable was calculated and used to measure respondents’ perception and to test the hypotheses.The descriptive technique employed statistically indicated that all audit function was perceived as important and effective. For perceived importance, the findings had indicated that the students highly expected auditor to enhance the reliability of financial statements, ensure the reports are prepared in accordance to GAAP and sufficiently carry out valuation on company liabilities. In term of effectiveness, they agree that the auditors have effectively delivered audit function such on performing independent opinion of financial report, auditing profession is self regulated and auditors have ensured that the preparation of financial statements are according to GAAP. Audit functions are also ranked based on their total mean.Finally, a comparison was made between results from the current and Reynolds’ study to identify how different group of users actually perceive audit functions that are currently being performed by audit practitioners.